2020
DOI: 10.1016/j.heliyon.2020.e05104
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, optical properties, and aging studies of natural pigments of various flower plants

Abstract: In this paper, we reported the extraction process of five different flowering plants utilizing different dye extraction methods and solvents (ethanol and water) to choose the best dye removal process. The FTIR spectra revealed the presence of several clear functional groups for all five natural dyes. The analytical studies such as UV spectroscopy, column chromatography, and vacuum evaporation were performed to isolate the dyes from their solutions. The UV-Vis studies on the pigments of flower extracts indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…The extraction process for FPCS was optimized as an improvement on the traditional solvent extraction method reported previously [ 28 ]. Response surface methodology (RSM) is commonly used to optimize complex extraction procedures as it can simultaneously evaluate the effects of different parameters, as well as their interactions [ 5 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The extraction process for FPCS was optimized as an improvement on the traditional solvent extraction method reported previously [ 28 ]. Response surface methodology (RSM) is commonly used to optimize complex extraction procedures as it can simultaneously evaluate the effects of different parameters, as well as their interactions [ 5 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Then, the mixture was passed through filter paper (Blue Ribbon, Grade 589, and Germany). Vacuum evaporator (Heidolphe, Germany) was used to concentrate the extracts, and lyophilizing was performed to obtain hydrous extract using freeze dryer (10).…”
Section: Methodsmentioning
confidence: 99%
“…It is produced by adding β -glucosidase to a mixture of cyclic enzyme glycosides extracted from gardenia fruit to produce kynepin [21] Although kynepin itself has no color, it can react with protein hydrolysis products to produce a blue substance, providing a new natural dye for the textile, cosmetic, and food industries. [9,22] . In addition to this, the preparation of natural blue pigments using metabolites produced by microbial cultures is now a major research target [23][24][25] .…”
Section: Natural Blue Pigmentmentioning
confidence: 99%
“…Natural blue pigments are susceptible to structural degradation and changes when subjected to external factors such as light, temperature and pH [9] , so it becomes essential to study the extraction conditions of the pigments. It was found that the methods of extraction of biological compounds from microalgae include supercritical fluid extraction [38] microwave-assisted extraction [39] extraction, pressurized liquid extraction [40] ultrasonic assisted extraction [41] and pulsed electric field treatment.…”
Section: Extraction Of Natural Blue Pigmentmentioning
confidence: 99%
See 1 more Smart Citation